(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
In this article, the History of Military Art of the Peoples of the Ancient World was the oldest classified societies in human history: Egypt, Syria, Iran, India, and China. This article is intended for familiarization with students of higher and secondary specialized institutions.